Entre pirâmides e círculos : um estudo sobre a central de práticas restaurativas do juizado regional da infância e juventude de Porto Alegre - Barboza, Iuscia Dutra (2013)
The present dissertation is the result of an experimental research which analyzed the institutionalization of restorative justice that was carried out by the Tribunal de Justiça of Rio Grande do Sul in the Juizado Regional da Infância e Juventude of the city of Porto Alegre through a formalization of the Central de Práticas Restaurativas. The main purpose of this work is to analyze how the institutionalization of restorative practices within the Juizado da Infância de da Juventude can contribute to a shift of paradigm in the judicial administration of conflicts. In order to do that, the theoretical framework of the sociologist Pierre Bourdieu was established as a starting point, from wich a portrait of the judicial field of administration of conflicts in Brazil was delineated, focusing on the judicial sub-field of childhood and youth, as well as traced an overview of the restorative justice movement for the purpose of analyzing the data collected in the case study. In conclusion, it is pointed out that restorative justice is in a process of consolidation as a proposal to be considered by the judicial actors in Brazil, and it seems safe to affirm that the Central de Práticas Restaurativas represented a fundamental contribution to this movement, in spite of its constitution not having resulted in a change on the professional habitus of the judicial agents that constitute the Juizado da Infância e da Juventude and, therefore, not having altered substantially the way of reproduction of this judicial space that was the object of the case study.